Indoor air quality assessment criteria in environmental certifications of buildings - Gobbi, Mirna Elias (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Considering the environmental certifications for buildings (AQUA-HQE, BREEAM, LEED and WEEL) that have become widespread in civil construction, and which can help in the construction of more sustainable environments, the objective of the research is to investigate the types of pollutants in environmental certifications. evaluated in the indoor air quality categories (IAQ) and analyze the proposed methods to obtain pollutant results. To meet the proposed objectives, criteria related to QAI were researched in each of the certifications. In the AQUA-HQE tool, the guide “Non-residential buildings under construction” (2022) and the “Health Organizations” (2011) were used. In BREEAM certification, the guide released in 2022 was used. In LEED, the “Indoor Environmental Quality” category (2019) was examined. In WEEL certification, the “Air Monitoring” category (2023). Environmental certifications for buildings address IAQ in different ways, but they all contain the subject, which demonstrates its relevance. The limits imposed on air contaminants demonstrate concerns regarding the health of building occupants. In general, the pollutant emission limits indicated in the certifications evaluated have similar values, only the formaldehyde limits showed considerable differences.
Keywords: Indoor air quality; Environmental certification; Construction